1985
DOI: 10.1073/pnas.82.23.8075
|View full text |Cite
|
Sign up to set email alerts
|

Cytotactin, an extracellular matrix protein of neural and non-neural tissues that mediates glia-neuron interaction.

Abstract: An extracellular matrix protein, cytotactin, with widespread tissue distribution has been identified, isolated, and partially characterized. Cytotactin mediates glia-neuron adhesion in vitro, but unlike Ng-CAM, the neuron-glia cell-adhesion molecule, it is absent from neurons. Cytotactin was isolated from 14-day embryonic chicken brains as structurally related polypeptides of Mr 220,000, 200,000, and 190,000. These polypeptides were efficiently extracted in the absence of detergent and appeared to be disulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
248
0
3

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(260 citation statements)
references
References 31 publications
9
248
0
3
Order By: Relevance
“…To date three members of the family have been identified in mammals: tenascin-C (TN-C), tenascin-R (TN-R), and tenascin-X (TN-X). TN-C, variably identified as myotendinous antigen (Chiquet and Fambrough, 1984), GMEM (Bourdon et al, 1985), cytotactin (Grumet et al, 1985), J1 (Kruse et al, 1985), hexabrachion (Erickson and Iglesias, 1984), or simply tenascin, is the prototype of this gene family. TN-C has widespread developmental expression and a variety of postulated morphogenetic functions (Chiquet-Ehrismann et al, 1986;Ruegg et al, 1989;Crossin and Hoffman, 1991;Tan et al, 1991;Julian et al, 1994;Young et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…To date three members of the family have been identified in mammals: tenascin-C (TN-C), tenascin-R (TN-R), and tenascin-X (TN-X). TN-C, variably identified as myotendinous antigen (Chiquet and Fambrough, 1984), GMEM (Bourdon et al, 1985), cytotactin (Grumet et al, 1985), J1 (Kruse et al, 1985), hexabrachion (Erickson and Iglesias, 1984), or simply tenascin, is the prototype of this gene family. TN-C has widespread developmental expression and a variety of postulated morphogenetic functions (Chiquet-Ehrismann et al, 1986;Ruegg et al, 1989;Crossin and Hoffman, 1991;Tan et al, 1991;Julian et al, 1994;Young et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Originally described in the chicken as myotendinous antigen [5,6], tenascin is identical or homologous to molecules discovered simultaneously by ,3thor laboratories: cytotactin in the chicken [7][8][9] ;.nd glioma mesenchymal extracellular matrix protein in human [10], It appears furthermore that tenascin is the predominant mouse component recognized by the Jt antibody [11].…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy studies have shown that tenascin has a six-armed structure with a central core named hexabrachion [9il [2][3][4][5][6][7][8][9][10][11][12][13][14]. The complete sequence of chicken tonE.seth [15][16][17][18] as well as part of that of human tenascin [19] have been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HNK-1 epitope has been shown to be present in various other glycoproteins, many of which are known to be involved in adhesive phenomena among neural cells. Among these are the neural cell adhesion molecules N-CAM (Kruse et al 1984), cytotactin (Grumet et al 1985), L1, L2, and Jl (Rathjen and Schachner 1984;Kruse et al 1985), and the myelinassociated glycoprotein (Poltorak et al 1987). In fish, the epitope has been shown to be present in a group of glycoproteins, called ependymins, that are secreted into the cerebrospinal fluid of goldfish during learning (Shashoua et al 1986) and in a subset of acetylcholinesterase molecules present in the electric organ of Electrophorus and Torpedo spp.…”
mentioning
confidence: 99%